Political participation of the chinese youth in market economy and implication on communist youth league - Kumar, Rakesh (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
Political participation entails citizens engagement to exert influence on the political process and policies in a desired direction. Therein, participation of the youth has significance as a transient yet constantly receiving community with potential to shape the course of history in any society. The activities and functions of youth organizations have been pivotal in effecting changes in the twentieth century Asian socio-political and economic realms. Under the similar circumstances, the Peoples Republic of China appears to be continuously evolving its social, economic, political and cultural regimes in response to the fluctuating demands of the citizens and the youth. This Essay fathoms changes in political participations of the youth in China, its implication on the Communist Youth League and how the Communist Youth League responds in the era of Market Economy.